IDENTIFIKASI KASUS CEDERA OLAHRAGA PADA PEMAIN SEPAK BOLA PUTRI PADA KLUB RAJAWALI GLOBAL CAKRAWALA - Fitriani Fitriani; Arimbi Arimbi; Saharullah Saharullah (Jurnal Ilara : Jurnal Hasil Penelitian, Aplikasi Teori, Analisa, Dan Pembahasan Kepustakaan tentang Keolahragaan, 2023)
This research is a descriptive research with a survey method. This study aims to determine the body parts and types of injuries that often occur in female soccer players at Rajawali Global Horizons (RGC) club with a total sample of 30 people by using a saturated sampling technique where saturated sampling is a sampling technique when all members of the population are used. as sample. The data collection technique in this study was to give a questionnaire to a number of respondents and the respondents filled out the questionnaire, after which the questionnaire was returned to the researcher. From the results of the descriptive analysis, it can be seen that cases of injury to the dominant body parts occurred in female soccer players at Rajawali Global Horizons, namely the legs and feet with a percentage of 53.11%, then the arms and hands by 27.55%, the head. 8.87%, spine 6.09%, and body part 4.37. The most dominant type of injury occurs in women's football at the Rajwali Global Horizons (RGC) club, namely bruises 27.54%, then sprains/ strain by 21.39%, fracture by 17.51%, dislocation 13.90%, abrasion by 10.70%, cramps by 6.68% , and the type of head injury (fainting) as the type of injury that is most rarely experienced, namely by 2.27%.